2022
DOI: 10.1039/d1se01889b
|View full text |Cite
|
Sign up to set email alerts
|

PVDF/Ag2CO3nanocomposites for efficient dye degradation and flexible piezoelectric mechanical energy harvester

Abstract: Now-a-days, the increasing demand of flexible, light weight and portable electronic devices for high energy storage are paramount for sensors and actuators. In this context, flexible piezoelectric polymer nanocomposite has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…To check the mechanical stability and durability of the CBIP3-based PENG for long-term power generation, a fatigue test is performed under up to ∼18,000 cycles when an impart force of 2.5 N is applied, and it shows constant current and voltage response of ∼0.8 μA and 1.8 V, respectively, for the whole duration (Figure a,b). Moreover, the mechanical pressure sensitivity curve of the PNG is measured for the pressure range of ∼0.5–50 kPa. , It is observed that the pressure sensitivity for the low-pressure (0.5–10 kPa) range is 44 mV/kPa and for the 10–50 kPa range it is 20 mV/kPa (Figure c). This decrease in sensitivity is probably due to the theoretical limits of effective strain in piezoelectric materials in the high-pressure region .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…To check the mechanical stability and durability of the CBIP3-based PENG for long-term power generation, a fatigue test is performed under up to ∼18,000 cycles when an impart force of 2.5 N is applied, and it shows constant current and voltage response of ∼0.8 μA and 1.8 V, respectively, for the whole duration (Figure a,b). Moreover, the mechanical pressure sensitivity curve of the PNG is measured for the pressure range of ∼0.5–50 kPa. , It is observed that the pressure sensitivity for the low-pressure (0.5–10 kPa) range is 44 mV/kPa and for the 10–50 kPa range it is 20 mV/kPa (Figure c). This decrease in sensitivity is probably due to the theoretical limits of effective strain in piezoelectric materials in the high-pressure region .…”
Section: Resultsmentioning
confidence: 91%
“…Consequently, the maximum generated piezo-potential of 4 V is reached and the maximum displacement occurs in this structure (Figure S7­(iv,vi)). The results indicate that the experimentally observed piezo-potential is in good agreement with the FEM simulated results . Moreover, a control device was fabricated entirely from PDMS without using a CBIP composite.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, the environment has been severely damaged since the industrial revolution [1] . The destruction of the environment threatened the survival and development of mankind [2–6] .…”
Section: Introductionmentioning
confidence: 99%